2020
DOI: 10.1101/2020.11.10.376293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong influence of vertebrate host phylogeny on gut archaeal diversity

Abstract: Commonly used 16S rRNA gene primers miss much of the archaeal diversity present in the vertebrate gut, leaving open the question of which archaea are host associated, the specificities of such associations, and the major factors influencing archaeal diversity. We applied 16S rRNA amplicon sequencing with Archaea-targeting primers to a dataset of 311 fecal/gut samples spanning 5 taxonomic classes (Mammalia, Aves, Reptilia, Amphibia, and Actinopterygii) and obtained from mainly wild individuals (76% were wild). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…This association may be driven by various host factors shared by flighted animals ( 65 ); however, body temperature is one such factor that has not yet been explored. Recently, our lab reported a positive correlation between abundance of the thermophilic archaeon Methanothermobacter and host body temperature across a range of mammalian and avian hosts ( 68 ). Although this correlation was inseparable from host phylogeny and might therefore be confounded by other host properties, it supports the hypothesis that host body temperatures can play a role in shaping gut microbiota composition.…”
Section: Temperature Optima Across the Tree Of Lifementioning
confidence: 99%
“…This association may be driven by various host factors shared by flighted animals ( 65 ); however, body temperature is one such factor that has not yet been explored. Recently, our lab reported a positive correlation between abundance of the thermophilic archaeon Methanothermobacter and host body temperature across a range of mammalian and avian hosts ( 68 ). Although this correlation was inseparable from host phylogeny and might therefore be confounded by other host properties, it supports the hypothesis that host body temperatures can play a role in shaping gut microbiota composition.…”
Section: Temperature Optima Across the Tree Of Lifementioning
confidence: 99%
“…Coevolution, an evolutionary process involving reciprocal selection between two or more species, is more likely to occur when the partners share a parallel evolutionary history, a pattern termed codiversification (1). Codiversification between members of the gut microbiota and their mammalian hosts has been suggested for specific gut bacteria, based on host phylogenies matching bacterial single-gene phylogenies (2)(3)(4). Using this approach in wild apes, Moeller et al (2016) demonstrated that several gut bacterial families codiversified with hominids over the last 15 million years (5).…”
Section: Main Textmentioning
confidence: 99%
“…Overall this work contributes substantially to the understanding of the microbiome as a complex multi-domain microbial network of the human gastrointestinal tract (Taffner et al 2018; Nayfach, Roux, et al 2020; Youngblut, Reischer, et al 2020; Youngblut, Cuesta-Zuluaga, et al 2020). We showed that despite the availability of more than 1,000 genomes, the human archaeome still remains undersampled.…”
Section: Discussionmentioning
confidence: 98%